Telaah Normatif Asas Persamaan Hukum (Equality Before The Law) Perkara Korupsi Dalam Pemberian Remisi - M. Wahyu Ramadhan; Adi Irawan; Asrarrudin; M. Tri Wahyudi; Era Marta Sari (Consensus : Jurnal Ilmu Hukum, 2024)
Applying the principle of justice before the law, also known as equality of law, when giving remission to prisoners involved in corrupt crimes. The study is normative. Remission will be given to qualified prisoners. The institute seeks to establish a system of seizure that enables the rehabilitation and re-socialization of prisoners involved in corrupt crimes. In short, the state must punish all criminals by providing good socialization to its society.